KOMODIFIKASI DAKWAH DALAM RELIGIOTAINMENT DI STASIUN TELEVISI INDONESIA - Fitri Murfianti (Institut Seni Indonesia Surakarta, 2012)
Dakwah program on television lately increasingly prevalent. Television stations compete for dakwah program package as attractive as possible so that your viewers by showing cool and popular ustadz or ustadzah. By television, religion is an integral part of the individual and society become commodities for profit. The media as an institution experiencing contradictions of capitalist profit-oriented and capital accumulation, because the mass media should be market-oriented and sensitive to the dynamics of market competition. The media should strive to deliver compelling information products that have a market advantage. Impressions of religion, in this case the spiritual spray or dakwah on television, packaged in such a way as to meet the tastes of the market. Dakwah program is not monotonous and messages are easily digested into magnets that sold a preacher. The commodification of dakwah on television is then colored portrait Indonesian dakwah on television. It was the scene of commercialization, media owners (producers) saw market share against the interest of religion.Keyword: Dakwah, Commodification